Two Inuit women and a child in costume on board whaling schooner Era, Hudson Bay, Canada - Comer, George (Creator) (Ownership Statement: Mystic Seaport, 1905)
Two Inuit women and a child in front of a sail back-cloth inside the deckhouse of the whaling schooner Era, Hudson Bay, probably March 8, 1905. One woman wears a beaded parka; both women wear cloth skirts. Infrastructure Lifestyle Title supplied by cataloger. Information from original envelope identifies this as # 39. The beads and cloth were obtained from the whalers and were popular trade goods. The schooner Era was built in 1847 at Boston, Massachusetts. She was a New London whaling vessel until her last voyage out of that port in 1892; her masters included James Monroe Buddington, John O. Spicer, and George Comer. She was wrecked off Miquelon Island, July 27, 1906. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment.